The Xylulose 5-Phosphate/Phosphate Translocator Supports Triose Phosphate, but Not Phosphoenolpyruvate Transport Across the Inner Envelope Membrane of Plastids in Arabidopsis thaliana Mutant Plants - Hilgers, Elke J. A.; Staehr, Pia; Flügge, Ulf-Ingo; Häusler, Rainer E. (Frontiers in Plant Science, 2018)
The xylulose 5-phosphate/phosphate translocator (PT) (XPT) represents a link between the plastidial and extraplastidial branches of the oxidative pentose phosphate pathway. Its role is to retrieve pentose phosphates from the extraplastidial space and to make them available to the plastids. However, the XPT transports also triose phosphates and to a lesser extent phosphoenolpyruvate (PEP). Thus, it might support both the triose phosphate/PT (TPT) in the export of photoassimilates from illuminated chloroplasts and the PEP/PT (PPT) in the import of PEP into green or non-green plastids. In mutants defective in the day- and night-path of photoassimilate export from the chloroplasts (i.e. knockout of the TPT [tpt-2] in a starch-free background [adg1-1]) the XPT provides a bypass for triose phosphate export and thereby guarantees survival of the adg1-1/tpt-2 double mutants. Here we show that the additional knockout of the XPT in adg1-1/tpt-2/xpt-1 triple mutants results in lethality when the plants were grown in soil. Thus the XPT can functionally support the TPT. The PEP transport capacity of the XPT has been revisited here with a protein heterologously expressed in yeast. PEP transport rates in the proteoliposome system were increased with decreasing pH-values below 7.0. Moreover, PEP transport determined in leaf extracts from wild-type plants showed a similar pH-response, suggesting that in both cases PEP2- is the transported charge-species. Hence, PEP import into illuminated chloroplasts might be unidirectional because of the alkaline pH of the stroma. Here the consequence of a block in PEP transport across the envelope was analyzed in triple mutants defective in both PPTs and the XPT. PPT1 is knocked out in the cue1 mutant. For PPT2 two new mutant alleles were isolated and established as homozygous lines. In contrast to the strong phenotype of cue1, both ppt2 alleles showed only slight growth retardation. As plastidial PEP is required e.g. for the shikimate pathway of aromatic amino acid synthesis, a block in PEP import should result in a lethal phenotype. However, the cue1-6/ppt2-1/ppt2-1 triple mutant was viable and even exhibited residual PEP transport capacity. Hence, alternative ways of PEP transport must exist and are discussed.